SELECTION OF CREATIVE ECONOMIC MSMEs FOR MINING COMMUNITIES IN LAHAT REGENCY USING ANALYTICAL HIERARCHY PROCESS - Puspita, M.; ., Bochori; Ibrahim, M. M.; Purba, D. A.; Almentirado, M. D.; Cahyaningsih, B. (Jurnal Pertambangan, 2024)
The sustainability of the mining industry is highly dependent on the availability of natural reserves of minerals. The conversion of land that was originally intended as a forest or garden into a mining area has caused people around the mine to change professions. However, professions or businesses that arise as a result of mining activities can only last as long as the mine is still operating. Then a big question mark arises regarding the sustainability of the community's economy after mining. With limited resources, MSMEs (micro, small and medium enterprises) based on the creative economy are one of the businesses that can be applied to empower post-mining communities. This study aims to determine the ranking of alternative creative economy MSMEs that can be developed in communities around the mine in Lahat Regency. The method used is the analytical hierarchy process (AHP). This study was conducted by determining the criteria for creative economy MSME businesses and alternatives and then continued with collecting primary data for paired comparisons using a questionnaire. Furthermore, data processing was carried out to determine alternative rankings and consistency ratio testing. The results of the study showed that the highest ranking of alternative creative economy MSMEs was the snack food culinary subsector, followed by the woven craft subsector, the textile craft subsector, and the traditional beverage culinary subsector in sequence.